Great food presentation : more than food on a plate - Video Education Australasia (Bendigo, Vic.: Video Education Australasia, 2022)
Shows the creative skills and knowledge required to produce great food presentations in 3 different settings: an opulent function venue, a suburban hospital with many ethnic patients and a busy food training program. Three participants outline their diverse operations and their holistic approach to good food presentation.